Using activity budgets and space use preferences to define enclosure appropriateness for African painted dogs, Lycaon pictus (Temminck 1820) - Somers, Michael J. (University of Pretoria, 2021)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2020.